A Methodology for Variability Reduction in Manufacturing Cost Estimating in the Automotive Industry based on Design Features - Romero Rojo, Francisco Javier; Roy, Rajkumar; Shehab, Essam (Cranfield University Press, 2009)
Small to medium manufacturing companies are coming to realise the increasing importance of performing fast and accurate cost estimates at the early stages of projects to address customers’ requests for quotation. However, they cannot afford the implementation of a knowledge-based cost estimating software. This paper explains the development and validation of a consistent methodology for the cost estimating of manufactured parts (focused on pistons) based on the design features. The research enabled the identification of the sources of variability in cost estimates, and the main one is the lack of formal procedures for the cost estimates in manufacturing SMEs. Finally, a software prototype was developed that reduces the variability in the cost estimates by defining a formal procedure, following the most appropriate cost estimating techniques.
Organised by: Cranfield University
Keywords: Cost estimating; manufacturing SMEs; process improvement; variability